The Internet-of-Things-based Fishpond Security System Using NodeMCU ESP32-CAM Microcontroller - Sumari, Arwin Datumaya Wahyudi; Annurroni, Ilyas; Ayuningtyas, Astika (Ikatan Ahli Informatika Indonesia (IAII), 2025)
Fish theft in ponds is a common problem, especially in freshwater fish farms. To solve this problem, a security system that can detect human movement and provide real-time notifications is needed. This research aims to design and implement an Internet of Things (IoT)-based fishpond security system using NodeMCU ESP32-CAM Microcontroller equipped with HB100 Radar Sensor to detect human entity movement with NodeMCU ESP32-CAM to take pictures of the approaching human entity, as well as Arduino Uno R3 to control system inputs and outputs. The system also sends real-time notifications and can be managed independently by a social media application. The results show that the system can detect human movement well, provide real-time notifications, and be handled easily. The test results show that the HB100 Radar Sensor can detect entities with a maximum distance of 9 meters with overall accuracy of 90%, the Buzzer performs well according to the human entity detected by the sensor, the Arduino Uno R3 successfully sends a trigger signal to NodeMCU ESP32-CAM to activate the OV2640 camera to capture the detected human entities with a maximum distance of up to 60 meters with an optimal distance between 1 to 9 meters. Integrated system test results show that all components of the fishpond security system